2021
DOI: 10.1177/0363546520981704
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular Injections of Mesenchymal Stem Cells Without Adjuvant Therapies for Knee Osteoarthritis: A Systematic Review and Meta-analysis

Abstract: Background: While many reviews have been performed to attempt to provide conclusive evidence regarding the outcomes of mesenchymal stem cells (MSCs) in osteoarthritis treatment, the evidence for MSC treatment in osteoarthritis remains contentious, as these reviews have been limited by the heterogeneous evidence available. Purpose: To pool the results of treatment using intra-articular injections of MSCs without any adjuvant therapies for osteoarthritis. Study Design: Systematic review and meta-analysis. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(54 citation statements)
references
References 41 publications
1
44
0
Order By: Relevance
“…68.18% (n=15) of the SRs/MAs included both RCTs and/or non-RCTs with different RoB and investigated the impact of RoB on results [11, 13, 27-32, 34, 35, 39, 42-45] (rated as "Yes"). Among the 15 SRs/MAs, two discussed the RoB resulting from methodological quality [13,27]; two mentioned the RoB of different study designs [28,32]; one reported the RoB of outcome measurement, blinding and randomization [29]; one addressed the RoB of outcome measurement, blinding, randomization, allocation concealment and selective reporting [11]; one discussed the RoB of methodological quality and study design [30]; two addressed the risk of selection bias [31,34]; one discussed the RoB caused by randomization and small sample size [35]; one reported the RoB of outcome measurement and blinding [39]; one discussed the RoB of implementation [42]; one addressed the RoB of outcome measurement and implementation [43]; one discussed the RoB caused by small sample size [44]; and one addressed the RoB of confounding factors [45]. The remaining 31.82% (n=7) of the SRs/MAs did not investigate the impact of RoB on the total effect [12, 33, 36-38, 40, 41] (rated as "No").…”
Section: Item 13* Results Interpretation With Risk Of Bias (Critical Item)mentioning
confidence: 99%
See 2 more Smart Citations
“…68.18% (n=15) of the SRs/MAs included both RCTs and/or non-RCTs with different RoB and investigated the impact of RoB on results [11, 13, 27-32, 34, 35, 39, 42-45] (rated as "Yes"). Among the 15 SRs/MAs, two discussed the RoB resulting from methodological quality [13,27]; two mentioned the RoB of different study designs [28,32]; one reported the RoB of outcome measurement, blinding and randomization [29]; one addressed the RoB of outcome measurement, blinding, randomization, allocation concealment and selective reporting [11]; one discussed the RoB of methodological quality and study design [30]; two addressed the risk of selection bias [31,34]; one discussed the RoB caused by randomization and small sample size [35]; one reported the RoB of outcome measurement and blinding [39]; one discussed the RoB of implementation [42]; one addressed the RoB of outcome measurement and implementation [43]; one discussed the RoB caused by small sample size [44]; and one addressed the RoB of confounding factors [45]. The remaining 31.82% (n=7) of the SRs/MAs did not investigate the impact of RoB on the total effect [12, 33, 36-38, 40, 41] (rated as "No").…”
Section: Item 13* Results Interpretation With Risk Of Bias (Critical Item)mentioning
confidence: 99%
“…In addition, 68.18% (n=15) of these SRs/MAs searched two or more databases, provided keywords and search strategy, and justi ed language or retrieval time restrictions, but supplementary retrieval contents (like published reviews, clinical trial registration platform, eld experts, gray literature) were not comprehensively searched. Among these SRs/MAs, one did not consult eld experts [11], while for the rest 14 SRs/MAs, one did not retrieve gray literature [43], three did not search the reference list of the included studies or gray literature [27,29,37], three did not search the clinical trial registration platform or gray literature [13,33,41], seven did not retrieve the reference list of the included studies, gray literature, or clinical trial registration platform [30,32,34,38,40,42,45], which met the minimal requirement (rated as "Partial Yes"). However, 31.82% (n=7) of the SRs/MAs failed to meet the minimal requirement (rated as "No"), among which, ve did not provide complete search strategies [28, 35,36,39,44], one did not explain the reason for restricting the English language [12], and one did not offer comprehensive search strategy or explain the reason for restricting the English language [31].…”
Section: Item 4* Literature Search (Critical Item)mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies suggested that the irreparable injury of the cartilage is a major challenge in the treatment of human osteoarthritis and tissue engineering is considered to be an innovative and promising therapy for the patients (Wang et al, 2020;Kader et al, 2021;Tan et al, 2021;Xia et al, 2021). Among various cell therapies, adipose-derived stem cell (ADSC) therapy appears to hold promise (Bistolfi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs) are increasingly being investigated in a number of different musculoskeletal conditions. MSCs have been investigated for osteoarthritis and chondral defects of the knee, ankle, and hip joints [1][2][3][4][5]. Similarly, MSCs have also been considered for the prevention and management of non-union or critical bone defects, but the data are not yet sufficient to determine their efficacy in these settings [6][7][8].…”
Section: Introductionmentioning
confidence: 99%